Advances in nanostructured materials and nanopatterning technologies (Advanced Nanomaterials Ser., 2020)
Advances in Nanostructured Materials and Nanopatterning Technologies: Applications for Healthcare, Environment and Energy demonstrates how to apply micro- and nanofabrication and bioextrusion based systems for cell printing, electrophoretic deposition, antimicrobial applications, and nanoparticles technologies for use in a range of green industry sectors, with an emphasis on emerging applications.